Advances In Gene Therapy For The Treatment Of Genetic Cardiovascular Disorders - Saeed, Zulqarnain; Rawat, Anurag; Abbas Bangash, Sudhair; Kartika Ririe, Avrina; Gupta, Anirudh; Akter Mitu, Momtaz; Tondas, Alexander Edo (Journal of Neonatal Surgery, 2025)
Background: Gene therapy has emerged as a promising treatment modality for various genetic disorders, including genetic cardiovascular diseases. These disorders, which are often inherited and lead to significant morbidity and mortality, have traditionally been managed through pharmaceutical interventions and lifestyle modifications. However, gene therapy presents a potential shift in treatment strategies, offering the possibility of addressing the root genetic causes of these disorders. This study aims to explore the current advancements in gene therapy for treating genetic cardiovascular disorders, examining its effectiveness, ethical considerations, and future prospects. Objective: The primary objective of this research is to evaluate the effectiveness and potential of gene therapy as a treatment for genetic cardiovascular disorders. The study seeks to understand the benefits, challenges, and ethical concerns related to the application of gene therapy in clinical settings. Additionally, the research examines the perceptions and expectations of participants regarding the future role of gene therapy in the treatment of genetic cardiovascular diseases. Methods: A survey-based research methodology was employed, targeting 130 participants with varying levels of familiarity with gene therapy and cardiovascular diseases. The survey included quantitative and qualitative questions, designed to gather data on participants' knowledge of gene therapy, their confidence in its effectiveness, perceived benefits, challenges, and ethical views. Data analysis was performed using descriptive statistics for quantitative responses and thematic analysis for qualitative feedback. Results: The results indicated that a significant portion of participants were familiar with gene therapy, but there were varying levels of confidence regarding its effectiveness. The majority of participants identified potential for a cure and improved quality of life as the primary benefits of gene therapy. However, concerns regarding ethical considerations and the lack of long-term data were prevalent. A substantial portion of respondents expressed optimism about the future role of gene therapy in treating genetic cardiovascular disorders, particularly if personalized approaches are adopted. Conclusion: Gene therapy holds substantial promise for the treatment of genetic cardiovascular disorders, with potential benefits including long-term efficacy and the possibility of a cure. However, challenges such as ethical concerns, regulatory issues, and the need for more robust long-term data remain significant barriers to widespread adoption. The future of gene therapy in this field will likely depend on overcoming these obstacles and further developing personalized treatment protocols. The findings suggest that while gene therapy is still in its experimental stages, it has the potential to revolutionize the treatment landscape for genetic cardiovascular disorders.